KERJASAMA â€œKEMITRAAN INDONESIA - AUSTRALIA UNTUK KESETARAAN GENDER DAN PEMBERDAYAAN PEREMPUANâ€ (MAMPU) DALAM MENGATASI PERMASALAHAN PEREMPUAN PEKERJA RUMAHAN DI DAERAH ISTIMEWA YOGYAKARTA - Nuranisa, Ezzah; Saepudin, Asep (Jurnal Bulletin, 2019)
This paper describes the existence and condition of women homeworkers (PPR/Perempuan Pekerja Rumahan) in the Special Region of Yogyakarta (DIY). Based on the data and analysis results show that the conditions of the PPR in the Special Region of Yogyakarta in particular and Indonesia in general have not received their proper rights as workers, as stated in the ILO Convention Number 177 of 1996. This is indicated by the existing laws and regulations in Indonesia, commitments and the support of the regional government has not guaranteed PPR rights. Therefore, through the MAMPU Program, in this case YASANTI strives for rights and protection for PPR is guaranteed social protection and rights as workers, such as other formal or informal workers. The MAMPU program carried out for this purpose is to increase the access of homeworkers to social protection programs and improve the conditions of women homeworkers and eliminate discrimination in the workplace. The program has succeeded in placing PPR as a group of workers who need to get social protection and be treated equally in their rights as workers, like other workers.